TECNOSINOS TALENTS PROGRAM: QUALIFYING AND CONNECTING YOUNG STUDENTS WITH TECHNOLOGY-BASED COMPANIES AT TECNOSINOS TECH PARK - Maldaner, Luis Felipe; Rucker, Thais (Revista Prâksis, 2019)
This article aims to fill a gap in academic studies in the sense of trying to approach the theory of practice in the training of young talent for technology-based companies, the main demand pointed out by companies within the Technological Park Tecnosinos. In order to do this, the authors carried out a follow-up of the activities of the Talents Program, developed since 2011 by the Tecnosinos team, to attract and encourage high school students from the Sinos Valley Region and also Unisinos University students for a career in technology and entrepreneurship. This is a study originated from a qualitative applied research with secondary data collection from Tecnosinos talents program activities. Additionally this work took primary data collection trough interview with students, Tecnosinos coordinator and company manager. The results are significant, because more than 8,000 students have participated in this program since its beginning and several of these students work in Tecnosinos companies today. Keywords: Talents. Tecnosinos Tech Park. Technology-based companies. RESUMO Este artigo tem por objetivo suprir uma lacuna nos estudos acadêmicos no sentido de procurar aproximar a teoria da prática na formação de jovens talentos para as empresas de base tecnológica, principal demanda apontada por empresas dentro do Parque Tecnológico Tecnosinos. Para isso, os autores realizaram um acompanhamento das atividades do Programa Talentos, desenvolvido desde 2011 pela equipe do Tecnosinos, para atrair e incentivar alunos de ensino médio da Região do Vale do Sinos e alunos da Universidade Unisinos para a carreira de tecnologia e para o empreendedorismo. Trata-se de um estudo originado de uma pesquisa qualitativa aplicada com dados secundários coletados das atividades do programa Tecnosinos Talentos. Adicionalmente este trabalho usou dados primários coletados em entrevistas com estudantes, com a coordenadora do Programa Talentos Tecnosinos e com um gerente de empresa. Os resultados são significativos, uma vez que mais de 8000 alunos já participaram desse programa desde o seu início e vários desses alunos trabalham hoje em empresas do Tecnosinos. Palavras-chave: Talentos. Parque Tecnológico Tecnosinos. Empresas de base tecnológica.